Exploring the potential mechanism of radix astragali against ischemic stroke based on network pharmacology and molecular docking - Yang Zhen; Xu Shan; Yongchun Li; Zhang Lin; Linlin Zhang; Ciai Lai; Fan Qin; ying Lv (Elsevier, 2022)
Objective: There are many prescriptions of traditional Chinese medicine (TCM) against ischemic stroke (IS) with radix astragali as the monarch medicine, such as Buyang Huanwu Decoction, in which the amount of radix astragali is as high as 120 g, we can see that radix astragali plays a significant role in the treatment of ischemic stroke. The research aims to define bioactive compounds, potential targets, pathways, and possible molecular mechanisms of radix astragali in treating IS based on network pharmacology and molecular docking techniques. Methods: Potential active compounds of radix astragali were collected from Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform Database (TCMSP), ETCM (Encyclopedia of Traditional Chinese Medicine), BATMAN-TCM (Bioinformatics Analysis Tool for Molecular Mechanism of TCM) and literature, and radix astragali targets were predicted using Swiss Target Prediction platform. GeneCards, TTD (Therapeutic Target Database), OMIM (Online Mendelian Inheritance in Man), and DrugBank were employed to retrieve IS-related targets. They were then overlapped to obtain intersections. Protein-protein interaction (PPI) network was constructed using STRING online database, and core targets were screened using network topology analysis. The biological function process and signaling pathways underlying key targets were executed using gene ontology (GO) and Kyoto encyclopedia of genes and genomes (KEGG) pathway, whereas enrichment and cluster analyses were conducted using Database for Annotation, Visualization, and Integrated Discovery (DAVID). Cytoscape 3.6.0 constructed the core target network and component-target-pathway network to analyze. Molecular docking to determine whether active compounds had a definite affinity for core targets by AutoDock Vina software. Results: In this study, 60 active compounds of radix astragali were obtained, together with 1098 corresponding targets, 1386 IS-related targets, and 279 intersecting target genes. Furthermore, ten key molecular targets of radix astragali for IS were collected, including AKT1, ALB, ACTB, TNF, IL6, IL1B, MAPK3, VEGFA, CASP3, and JUN. The key KEGG signaling pathways mainly include PI3K-Akt signaling pathway, neuroactive ligand-receptor interaction, cAMP signaling pathway, Ras signaling pathway, HIF-1 signaling pathway, Rap1 signaling pathway, MAPK signaling pathway, and TNF signaling pathway. Further molecular docking results indicated that the two main compounds had a high affinity for the three core targets. Conclusions: This study established that practicable mechanisms of radix astragali against IS would be linked to neuroprotective effects, improved cerebral blood flow, apoptosis inhibition of cerebral ischemia tissue cells, mediating inflammation, and radix astragali may be used as the effective traditional Chinese medicine in clinical treatment of IS .